2021
DOI: 10.2196/25549
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Professional Experiences With Virtual Antenatal Clinics During the COVID-19 Pandemic in a UK Tertiary Obstetric Hospital: Questionnaire Study

Abstract: Background The COVID-19 pandemic required rapid implementation of virtual antenatal care to keep pregnant women safe. This transition from face-to-face usual care had to be embraced by patients and professionals alike. Objective We evaluated patients’ and professionals’ experiences with virtual antenatal clinic appointments during the COVID-19 pandemic to determine satisfaction and inquire into the safety and quality of care received. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 23 publications
1
30
0
2
Order By: Relevance
“…The COVID-19 pandemic has been an essential examination of the robustness of virtual care models applied in primary care. 18 21 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 pandemic has been an essential examination of the robustness of virtual care models applied in primary care. 18 21 …”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported a high level of satisfaction with phone clinics by pregnant women. In the United Kingdom, the study by Quinn et al 21 reported that 86% rated their experience as good or very good. Liu et al 19 reported that women stated being very or extremely satisfied (27.9%) or moderately satisfied (43.5%) with their virtual prenatal experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Five studies (Madden 2020, provided qualitative data on televisits for routine antenatal care. [64][65][66][67][68] Four studies were based in the United States and one study was based in England.…”
Section: Qualitative Evidence Pertaining To Televisitsmentioning
confidence: 99%
“…Quinn 2021 sought to assess the experiences of patients and healthcare providers with virtual antenatal clinic appointments during the COVID-19 pandemic. 67 The study sent questionnaires with open-ended responses to 240 patients and 45 healthcare professionals (both clinical staff delivering virtual care and clerical staff organizing virtual care) in a tertiary obstetric unit in Leicester, England who experienced at least one virtual consultation. The patient and healthcare professional surveys had a 62% (148/240) and 82% (37/45) response rate, respectively.…”
Section: Qualitative Evidence Pertaining To Televisitsmentioning
confidence: 99%
“…One of the most commonly reported covid-related changes to all forms of service provision in maternity care has been an increase in the use of remote/virtual consultations using telephone or video 4 7 10–18. For example, one recent survey of all 194 obstetric units in England (42% response rate) found that 89% reported using digitally delivered consultation methods in antenatal care and 56.8% for postnatal care 7.…”
Section: Introductionmentioning
confidence: 99%